Demotivation Factors in Using English as Daily Communication in EFL School: Case Study of EFL Learners - Hizbul Wathoni; Ari Safar Wadi; Hanofi Harianto; Ab.Aziz Bin Sulaiman; Selamet Riadi Jaelani (Universitas Hamzanwadi, 2022)
This study aimed to describe the causes of students' demotivation in using English for daily communication and find its solutions. The present researcher used the descriptive qualitative method. It was conducted on EFL Learners. There were 15 students to be participants in this study. The data were collected by observing, interviewing, and giving questionnaires to participants about English usage in their Islamic boarding schools. The participants' answers and the video of their daily communication were analyzed by interpreting the handy camera and checking the result of interpretation to the result of questioner and interview. Second, the present researcher compared the result of the handy camera, questioner, and interview to the existing theory to determine the causes of students' demotivation in using English as daily communication and its solution. The result analysis showed that the cause of students' demotivation is their lack of ability to use English, especially in mastering vocabulary and its pronunciation. Other factors were learning contents and materials, teachers, and failure experience. In addition, they prefer to use Arabic because Arabic has been rooted as daily communication in that Islamic boarding school. In comparison, the solution for that problem is that the teachers should pay considerable attention to the students' English ability, especially mastering and pronouncing vocabulary. Also, the teachers are suggested to pay more attention to teaching methods and their behavior to increase students' motivation and interest in second language learning. In addition, the teachers should explicitly make a regulation to divide a period for the student to speak English and Arabic.